Impact of breastfeeding positions on neck pain in postpartum mothers - Dandekar, Simin A.; Khatavkar, Mayuri (International Journal Of Community Medicine And Public Health, 2022)
Background: Breastfeeding mothers often encounters various complaints such as pain and discomfort. It was also seen that a mother has to attain feeding position for a long period of time. Thus, our aim was to find if there is any correlation between musculoskeletal neck pain and breastfeeding position in post-partum mothers. Methods: It was a cross sectional, observational study in which sampling was done by purposive method. 207 postpartum mothers fulfilling inclusion criteria were included and a self-made questionnaire and neck disability index (NDI) were used as outcome measure. Statistical analysis was done using statistical package for the social sciences (SPSS) version 24. Results: Almost all those mothers reported neck pain while breastfeeding in different positions especially in side-lying and cross-cradle in terms of NDI with median value of 11.1 and there were 65.7% mothers who had awareness about ideal breastfeeding position. The interpretation of neck pain showed changes with respect to different positions, when analyzed by Kruskal Wallis test. Conclusions: Though it showed statistical insignificance in correlation due to various reasons such as negligence, habitualisation, lack of awareness, unmet support from family.